Recent advances in self-targeting natural product-based nanomedicines - Haifan Liu; Xingyue Jin; Suyi Liu; Xinyue Liu; Xiao Pei; Kunhui Sun; Meifang Li; Ping Wang; Yanxu Chang; Tiejie Wang; Bing Wang; Xie-an Yu (Journal of Nanobiotechnology)
Abstract Natural products, recognized for their potential in disease prevention and treatment, have been integrated with advanced nano-delivery systems to create natural product-based nanomedicines, offering innovative approaches for various diseases. Natural products derived from traditional Chinese medicine have their own targeting effect and remarkable therapeutic effect on many diseases, but there are some shortcomings such as poor physical and chemical properties. The construction of nanomedicines using the active ingredients of natural products has become a key step in the modernization research process, which could be used to make up for the defects of natural products such as low solubility, large dosage, poor bioavailability and poor targeting. Nanotechnology enhances the safety, selectivity, and efficacy of natural products, positioning natural product-based nanomedicines as promising candidates in medicine. This review outlines the current status of development, the application in different diseases, and safety evaluation of natural product-based nanomedicines, providing essential insights for further exploration of the synergy between natural products and nano-delivery systems in disease treatment. Graphical Abstract